2007
DOI: 10.1007/s00595-007-3501-0
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Fetoprotein-Producing Early Gastric Cancer of the Remnant Stomach: Report of a Case

Abstract: A 67-year-old man initially underwent a distal gastrectomy for early gastric cancer (T1, N0, M0; Stage IA) in March 1995. During the follow-up period, an elevation of the serum alpha-fetoprotein (AFP) level (98.8 ng/ml) and a liver tumor (S4) were detected. A left hepatectomy was performed in December 1996. Immunohistochemically, AFP-positive cells were present in both the primary gastric tumor and metastasized liver tumor. The serum AFP level normalized immediately, but it elevated again to 22.4 ng/ml. An end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 13 publications
(30 reference statements)
1
21
0
Order By: Relevance
“…quently described and is associated with a poor prognosis for vascular invasion, regional lymphadenopathy and frequent liver metastases [1][2][3][4][5] . Terracciano et al [6] showed positivity in virtually all HACs for AFP, cytokeratin-8 (CK-8), CK-18 and carcinoembryonic antigen, markers underlining its hepatoid nature, the contemporary positive staining for CK-19 and CK-20, and the frequent negativity of Hep Par1 in both primary tumors and their metastases.…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…quently described and is associated with a poor prognosis for vascular invasion, regional lymphadenopathy and frequent liver metastases [1][2][3][4][5] . Terracciano et al [6] showed positivity in virtually all HACs for AFP, cytokeratin-8 (CK-8), CK-18 and carcinoembryonic antigen, markers underlining its hepatoid nature, the contemporary positive staining for CK-19 and CK-20, and the frequent negativity of Hep Par1 in both primary tumors and their metastases.…”
Section: Case Reportmentioning
confidence: 99%
“…Several case reports of alpha-fetoprotein (AFP) producing gastric cancer have been described [1][2][3][4][5] . It represents 3.9%-11% of all the neoplasia of the stomach collected in a Japanese series.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AFP-producing tumors have been reported in several different organs, and commonly in the stomach [4][5][6][7][8] . The proportion of gastric cancers that secrete AFP has been reported to be 2.7%-8.0% [9] . AFP-producing gastric carcinomas have high proliferative activity and are associated with low levels of apoptosis and rich neovascularization.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] (Table 1) AFP producing gastric cancer (AFPGC) constitutes only about 2.7% to 8% of all gastric cancers. 10 They have high metastatic potential and possibility of vascular invasion, liver and lymph nodal metastases resulting in poor prognosis. 2 In situations where associated liver mass is seen, it may be mistaken for coexistent hepatocellular carcinoma, like the index case.…”
mentioning
confidence: 99%